Mechanistic insight into protein modification and sulfur mobilization activities of noncanonical E1 and associated ubiquitin‐like proteins of Archaea. (October 2016) - Hepowit, Nathaniel L.; de Vera, Ian Mitchelle S.; Cao, Shiyun; Fu, Xian; Wu, Yifei; Uthandi, Sivakumar; Chavarria, Nikita E.; Englert, Markus; Su, Dan; Sӧll, Dieter; Kojetin, Douglas J.; Maupin‐Furlow, Julie A.
Abstract : Here we provide the first detailed biochemical study of a noncanonical E1‐like enzyme with broad specificity for cognate ubiquitin‐like (Ubl) proteins that mediates Ubl protein modification and sulfur mobilization to form molybdopterin and thiolated tRNA. Isothermal titration calorimetry and in vivo analyses proved useful in discovering that environmental conditions, ATP binding, and Ubl type controlled the mechanism of association of the Ubl protein with its cognate E1‐like enzyme (SAMP and UbaA of the archaeon Haloferax volcanii, respectively). Further analysis revealed that ATP hydrolysis triggered the formation of thioester and peptide bonds within the Ubl:E1‐like complex. Importantly, the thioester was an apparent precursor to Ubl protein modification but not sulfur mobilization. Comparative modeling to MoeB/ThiF guided the discovery of key residues within the adenylation domain of UbaA that were needed to bind ATP as well as residues that were specifically needed to catalyze the downstream reactions of sulfur mobilization and/or Ubl protein modification. UbaA was also found to be Ubl‐automodified at lysine residues required for early (ATP binding) and late (sulfur mobilization) stages of enzyme activity revealing multiple layers of autoregulation. Cysteine residues, distinct from the canonical E1 'active site' cysteine, were found important in UbaA function supporting a model that this noncanonical E1 is structurally flexible in its active site to allow Ubl~adenylate, Ubl~E1‐like thioester and cysteine persulfide(s) intermediates to form. Abstract : Here we report the first detailed biochemical study of an E1‐like enzyme (UbaA) that forms diverse ubiquitin‐like (Ubl) protein conjugates and mobilizes sulfur to generate thiolated tRNA and molybdopterin. Importantly, UbaA is found autoregulated by Ubl‐protein modification and structurally flexible to allow Ubl~adenylate, Ubl~E1 thioester and persulfide(s) intermediates to form in the absence of a canonical E1 active site cysteine.